Prevalence of Gastrointestinal Bleeding in Patients Receiving Dual Antiplatelet Therapy after Percutaneous Coronary Intervention - Ahsan Ali, Junaid Almas, Muhammad Zubair, Muhammad Khan Soomro, Shumaila Israr, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Dual antiplatelet therapy (DAPT), consisting of aspirin and a P2Y12 inhibitor such as clopidogrel, prasugrel, or ticagrelor, is an essential component of post–percutaneous coronary intervention (PCI) management to prevent stent thrombosis and recurrent ischemic events. Objective: To determine the prevalence of gastrointestinal bleeding and associated risk factors among patients receiving dual antiplatelet therapy after percutaneous coronary intervention. Methodology: This descriptive cross-sectional study was conducted at Punjab Institute of Cardiology, Lahore from November 2022 to April 2023. A total of 85 patients who underwent PCI and were receiving DAPT (aspirin with clopidogrel, prasugrel, or ticagrelor) were included. Demographic data, comorbidities, duration of therapy, and use of proton pump inhibitors (PPIs) were recorded. Results: The mean age of participants was 59.8 ± 10.4 years, with 68.2% males and 31.8% females. The overall prevalence of gastrointestinal bleeding was 12.9% (11 patients), with upper GI bleeding accounting for 72.7% and lower GI bleeding for 27.3% of cases. Significant associations were observed between GI bleeding and chronic kidney disease (p = 0.02) as well as absence of PPI use (p = 0.03). Although not statistically significant, the highest bleeding incidence was noted among patients receiving aspirin plus prasugrel (21.4%), compared with aspirin plus clopidogrel (9.8%) and aspirin plus ticagrelor (10%). Conclusion: It is concluded that gastrointestinal bleeding is a frequent and clinically important complication among patients on DAPT following PCI, with a prevalence of approximately 13%. Keywords: dual antiplatelet therapy, percutaneous coronary intervention, gastrointestinal bleeding, proton pump inhibitors.